REMOVAL OF NAPTHOL DYE FROM BATIK WASTEWATER USING CHITOSAN FROM BLACK SOLDIER FLY PUPAL EXUVIAE - Putri Rayhani Rahmania; Arseto Yekti Bagastyo (Jurusan Kimia FMIPA Universitas Lampung, 2024)
This research discussed about the application of chitosan from black soldier fly (BSF) pupal exuviae as an adsorbent in the adsorption of napthol dyes in batik wastewater. The adsorption process was carried out in batch process with the aim of analyzing the dye removal efficiency and adsorption capacity as affected by solution pH and adsorbent dosage, as well as determining the appropriate adsorption kinetics model to be applied. Changes in dye concentration were analyzed for absorbance using a spectrophotometer. The results of the adsorption process research showed that the optimal pH and adsorbent dose were at pH 4 and 0.4 g/L with removal efficiency reaching 92%. The removal efficiency decreased with increasing pH. The increasing amount of adsorbent, the removal efficiency decreased. However, after reaching the optimal dose, the addition of chitosan mass no longer gave a significant increase in the removal efficiency, indicating that the saturation point had been reached. The adsorption process tends to follow a pseudo second-order kinetics model with a maximum adsorption capacity of 344.82 mg/g.